From damage control to sustainable development: European development policy under the next EU budget - Svea Koch; Niels Keijzer; Christine Hackenesch; Julian Bergmann (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The EU is one of the leading global players in international development, trade, peace and security. Therefore, a key part of the EU's Multiannual Financial Framework (MFF) is the one reserved for action beyond EU's borders. This budget heading is called `Global Europe' (also referred to as Heading IV). Under the current budget for the period of 2014 to 2020, including the inter-governmental European Development Fund (EDF), over 90 billion euros are available for the EU's external action. The lion's share of this is reserved for development cooperation. In previous years, the EU has dealt with new challenges in external action mostly by creating specific initiatives and new financial instruments. At the start of the negotiations on the next MFF, Heading IV thus appears to be rather complex and fragmented compared to other headings. In addition to the fragmentation of the instruments, the EU has also failed to make clear strategy level choices. Recent EU strategies create an impression that nearly everything is a priority, overstretching the EU's financial as well as implementation capacity. This lack of a clear direction has allowed member states' governments to put forward their own strategic interests (mostly related to migration and sec¬urity). Given the tight budget situation of the EU, a clear direction for Heading IV needs to be developed that helps to address a number of bottlenecks and trade-offs. These relate to (i) the overall volume, (ii) the thematic choices, (iii) the re¬cipients of EU funding and (iv) the architecture of Heading IV. Concerning volume, it is important to acknowledge that the other, larger budget headings will determine the budgetary space for EU development policy. Despite discussions on increasing member state contributions, Brexit is likely to result in a smaller overall budget. New political priorities (such as migration and security) are expected to further squeeze funding for sustainable development. Choices thus need to be made in terms of issues and geographic focus. As for the thematic choices, the short-term involvement in crisis response needs to be combined with a clear strategy for engaging with partners on the 2030 Agenda and SDGs through geographic and thematic programmes. The partners' SDG strategies and the EU's added value should guide this engagement. Geographically, the EU needs to strike a balance between the cooperation with middle-income countries (MICs) and a focus on the poorest countries. This can only be achieved by focusing geographic allocations to LDCs, neighbouring countries and sub-Saharan Africa, while engaging with MICs in other regions through thematic programmes. In addition, Heading IV needs to be strongly rationalised, both in terms of the number of instruments and initiatives and of the rules for managing these. A key prerequisite in this regard – also for the proposal of a single instrument in Heading IV – would be the `budgetisation' of the inter¬governmental EDF, which would allow for a truly European development policy.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Entwicklungsfinanzierung und öffentliche Finanzen